Deteksi Resistensi Amoxicillin Helicobacter pylori pada Pasien Dispepsia - Indah Sulistiyawati; I Gede Arinton; Hendro Pramono (Fakultas Biologi | Universitas Jenderal Soedirman, 2016)
Amoxicillin is one of the antibiotics that commonly used on treatment of H. pylori infection. pbp1A gene mutation in H. pylori is a dominant cause of amoxicillin resistance. This study was aimed to evaluate the presence of H. pylori in patients with dyspepsia by using non-invasive method i.e. H. pylori stool antigen (HPSA) and invasive method i.e. pbp1A gene amplification, and also evaluate the amoxicillin resistance of H. pylori by assessing the pbp1A gene mutations. The samples were 26 faeces and 26 gastric biopsies of patients with dyspepsia from the Internal Disease of Prof. Dr. Margono Soekardjo Hospital in Purwokerto. DNA amplification performed by using polymerase chain reaction (PCR) to detect the presence of amoxicillin resistance encoding gene i.e. penicillin binding protein (pbp1A). Sequencing of the DNA sample was performed at the First Base Malaysian Company, to analyze the existence of a point mutation. DNA sequencing analysis of 12 samples showed the presence of a mutations in pbp1A gene from 2 samples, in the third motive of pbp i.e. amino acid changes, Alanine 599 substituted to Threonin and Threonin 592 to Alanine. Those mutations become a dominant risk factor for resistance of H. pylori, toward the bacterial peptidoglycan synthesis. In this research, it was known that the detection of H. pylori infection by using PCR remains more accurate and specific method. The presence of H. pylori mutant strains in this study may becomes the risk factors of resistance to amoxicillin treatment.